PENINGKATAN KEMAMPUAN MEMBACA ANAK MELALUI METODE FONIK DI TAMAN KANAK-KANAK ISLAM ADZKIA BUKITTINGGI - Nopriyanti, Leni (Jurnal Ilmiah Pesona PAUD, 2012)
This study motivated the child's ability to read low because there is exactly the method used by teachers. The purpose of this study to improve the reading skills of children through fonik method with the type of research is a class act. Implemented in kindergarten Adzkia Bukittinggi Islam. Data collection techniques used observation and documentation. The results in the first cycle increased but not maximized in the second cycle continue to increase beyond the average minimum passing grade indicating that the method fonik improve reading skills of children